A Practical Guide to Using the Positive Deviance Method in Health Services Research. (28th June 2016) - Rose, Adam J.; McCullough, Megan B.
Abstract : Objective: To provide practical tips for health services researchers considering the use of positive deviance (PD) methods to help explain variations in quality of care or other meaningful parameters. Data Sources: Published literature and personal experience. Study Design: Narrative review. Principal Findings: This review includes a discussion of possible applications of PD to health services research, some methodological choices applicable to PD, and some brief tips regarding publishing the results and incorporating them into future interventions. Conclusions: It is hoped that this article will help health services researchers to use this valuable research method more effectively, especially those who have not done so before.